The Effectiveness of Providing Direct Versus Indirect Written Corrections on the Grammar of Lebanese Sixth-Grade Students Learning English as a Foreign Language - Baasiri, Buna Khaled (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2025)
This study employed a mixed-methods approach, combining a quasi-experiment and Think-Aloud Protocols, to examine how direct and indirect written corrective feedback affected the grammatical accuracy of English as a Foreign Language (EFL) among sixth-grade students in Lebanon. The quantitative findings indicated that both feedback types improved accuracy during revision, with direct feedback showing a stronger immediate impact. Notably, indirect feedback led to better immediate learning of comparative structures. Qualitative data suggested similar levels of understanding during error correction across groups, highlighting the need to consider individual learner characteristics and error types when providing written feedback. Ultimately, the research offers key insights into the effectiveness of different feedback methods and the factors influencing their success in language learning, emphasizing personalized and cognitively informed feedback practices. Keywords: effectiveness, written corrective feedback, grammatical accuracy, learners, quasi-experiment, Think-Aloud Protocols, initial language proficiency, target linguistic structures, short-term learning, long-term retention, quantitative results